2016
DOI: 10.1111/jvp.12363
|View full text |Cite
|
Sign up to set email alerts
|

Residue depletion of amoxicillin and its major metabolites in eggs

Abstract: The depletion of amoxicillin (AMO) and its major metabolites, amoxicilloic acid (AMA) and amoxicillin-diketopiperazine-2',5'-dione (DIKETO) in the albumen, yolk and whole egg was studied after the oral dose of AMO (25 and 50 mg/kg body weight) to laying hens once per day for five consecutive days. Egg samples were prepared by a simple liquid-liquid extraction procedure with acetonitrile and saturated methylene chloride and analysed using liquid chromatography-tandem mass spectrometry. The results showed that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…2 AMO is official in British Pharmacopeia (BP), 1 European Pharmacopeia (EP) 3 and United States Pharmacopeia (USP) 4 , they include HPLC method for its determination. It is still a limited number of analytical methods that are reported for the determination of AMO including kinetics degradation, [5][6][7] spectrophotometric, [8][9][10][11][12][13] UHPLC UPLC and mass spectrometry, [14][15][16][17][18][19] thin layer chromatography (TLC), [20][21][22] capillary electrophoresis, [23][24][25][26] high performance liquid chromatography (HPLC), [27][28][29][30][31] in vitro dissolution studies, [32][33][34][35][36] amoxicillin residues in animal tissues using SPE-LC, 37 SPE-cation exchange, 38 in eggs using HPLC-FLD, 39 or HPLC-MS 40 and in commercial meat and milk samples 41 using HPLC-FLD. According to the best of our knowledge there is no validated method for the determination of amoxicillin residues and application to cleaning machine in pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…2 AMO is official in British Pharmacopeia (BP), 1 European Pharmacopeia (EP) 3 and United States Pharmacopeia (USP) 4 , they include HPLC method for its determination. It is still a limited number of analytical methods that are reported for the determination of AMO including kinetics degradation, [5][6][7] spectrophotometric, [8][9][10][11][12][13] UHPLC UPLC and mass spectrometry, [14][15][16][17][18][19] thin layer chromatography (TLC), [20][21][22] capillary electrophoresis, [23][24][25][26] high performance liquid chromatography (HPLC), [27][28][29][30][31] in vitro dissolution studies, [32][33][34][35][36] amoxicillin residues in animal tissues using SPE-LC, 37 SPE-cation exchange, 38 in eggs using HPLC-FLD, 39 or HPLC-MS 40 and in commercial meat and milk samples 41 using HPLC-FLD. According to the best of our knowledge there is no validated method for the determination of amoxicillin residues and application to cleaning machine in pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…Sultamicillin is hydrolyzed into sulbactam and ampicillin by enterolactase in the intestinal wall after oral administration [ 11 , 34 , 35 ], so it is speculated that AS hydrolyzed in vivo to amoxicillin and sulbactam. Because amoxicillin is easily metabolized to amoxicilloic acid (AMA) and amoxicillin diketopiperazine (DIKETO) [ 36 , 37 ], it is speculated that some of the amoxicillin will be metabolized to these compounds in vivo. It has been reported that sulbactam exists mainly in the archetypal form in rats [ 38 , 39 ], so it is speculated that sulbactam exists in rats.…”
Section: Resultsmentioning
confidence: 99%
“…Baere et al (2002) developed a quantitative assay for AMO, AMA and DIKETO in animal tissues and described the long-term presence of AMA as a metabolite of AMO in kidney and liver samples of swine. In practice, AMO metabolites have lost the antimicrobial activity of the parent compound (Liu et al, 2017); however, the metabolites, AMA and DIKETO, have been reported to be allergens (Fagerquist et al, 2005;Reyns et al, 2008a). Therefore, AMA residues should be determined to ensure the safety of animal-derived foods despite MRLs for the metabolites of AMO not being specified.…”
Section: Discussionmentioning
confidence: 99%